Sistem Informasi Penjualan Diamond Mobile Legends Di Moro Cell Berbasis Web - Santosa, Dwi; Mustafidah, Hindayati (ITB Ahmad Dahlan Jakarta, 2021)
The transaction process in purchasing a game feature often makes it difficult for someone to make a purchase of game features so that a third party is needed to make it easier to purchase features in the game. However, there are problems where related parties need a means to attract customers as a means of promoting products sold by related parties, therefore it is necessary to have a system where in the system there is a useful feature to attract customers. From there, a diamond sales information system for Mobile Legends was built for the Moro Cell company as a means to attract customers. In the development of this system there are steps that are carried out, namely analysis, design, implementation, testing and maintenance of these steps a system is built that can be used to purchase a diamond which aims to attract customer interest with a feature contained in it, namely a member feature that can provide a 5% discount to customers for every diamond purchase transaction. The result of this research is that a diamond sales information system for Mobile Legends has been built in Moro Cell that can help users make diamond purchases and can attract customers from Moro Cell. With this sales system, users are more helped by the transaction process provided by the system and some users are interested in some of the offers in this system such as the member features offered in this system.